A longitudinal study of change in falls risk and balance and mobility in healthy older people and people with Alzheimer disease - Suttanon, P.; Hill, Keith; Said, C.; Dodd, K. (Lippincott Williams and Wilkins, 2013)
Objective: The aim of this study was to determine the rate of change in falls risk and balance and mobility performance in people with Alzheimer disease (AD) compared with those of healthy older people over a 1-yr period.Design: A 1-yr follow-up study of change in levels of falls risk, balance, and mobility performance in 15 community-dwelling older people with mild to moderate AD and 15 healthy age-matched older people was conducted. Each participant completed a comprehensive assessment of balance and mobility, falls and falls risk and level of physical activity at baseline and 1yr later.Results: The rate of increase in the number of falls and risk of falling was greater in people with AD. The rate of deterioration on a number of balance and mobility measures was also significantly greater in people with AD compared with the healthy older people.Conclusions: People with mild to moderate AD have an increased rate of decline in falls risk, balance, and mobility over a 12-mo period compared with age-matched healthy older people. Given this increased rate of decline, intermittent review of falls, balance and mobility, and interventions to address identified contributory risk factors should be considered by health practitioners.